Porous activated carbon materials from Triphala seed stones for high-performance supercapacitor applications - Gnawali, Chhabi Lal; Shahi, Sabina; Manandhar, Sarita; Shrestha, Ganesh Kumar; Adhikari, Mandira Pradhannanga; Rajbhandari, Rinita; Pokharel, Bhadra P. (BIBECHANA, 2023)
Porous activated carbon materials derived from biomass could be the suitable materials for high-rate performance electrochemical supercapacitors as it exhibits high surface area due to well-defined pore structure. Here, we report the novel porous activated carbon from Triphala seed stones by chemical activation with zinc chloride at different carbonization temperature (400-700 °C) under the nitrogen gas atmosphere. The activated carbon was characterized by Fourier transform-infrared (FTIR) spectroscopy, Raman scattering and scanning electron microscopy (SEM). Nitrogen adsorption-desorption measurements was used to study the surface properties (effective surface areas, pore volumes and pore size distributions). The electrochemical measurements were performed in an aqueous 1 M sulphuric acid (H2SO4) solution in a three-electrode cell set up. Triphala seed stones-derived porous carbon materials with well-defined micro- and mesopores exhibit high specific surface area ranges from 878.7 to 1233.3 m2 g-1 and total pore volume ranges from 0.439 to 0.626 cm3 g-1. The specific capacitance obtained by electrochemical measurement experiment was 208.7 F g-1 at 1 A g-1. These results indicate that the prepared nanoporous activated carbon material from Triphala seed stones would have significant possibility as supercapacitor electrode material for high-energy-storage supercapacitor applications.